Exploitation of Gynoecious Lines in Cucumber (Cucumis Sativus L.) for Heterosis Breeding - Sharma, Madhu; Singh, Yudhvir; Singh, Shailesh Kumar; Dhangrah, V. K. (International Journal of Bio-resource and Stress Management, 2023)
Despite being native of India and having sufficient genetic variability, very meagre work has been done for the improvement of cucumber. To tide over the situation, there is a need to make concerted efforts to develop location specific hybrids having desirable horticultural and quality traits, and to make available their seeds to the farmers at a reasonable price. Moreover, cucumber crop is predominantly monoceious in nature but gynoecious sex form has also been reported that facilitates hybridization by reducing labour cost for crossing. Thus, to overcome the said problem; five gynoecious lines ‘EC-5082, Plp-Gy-1, G-1, G-3 and PCUCP-4’ and eleven testers ‘KL-1, K-pap, Japanese Long Green, Poinsette, DPC-1, EC-173934, Summer Green, K-90, Sel-75-2-10, K-75 and KL-3’ were crossed to derive fifty five crosses. The crosses and parents along with 2 standard checks were evaluated at Palampur and Bajaura in Himachal Pradesh, India. The pooled analysis of variance over locations revealed significant differences due to location, genotype and location×genotype for all the characters. Significant range of heterobeltiosis and standard heterosis was recorded among crosses for all characters. As many as 50 cross over better parent, 42 cross over standard check 1 and 41 cross over standard check 2 exhibited positive heterosis for marketable yield vine-1. The cross Plp×K-pap exhibited maximum positive heterosis over standard checks for marketable yield vine-1 and sufficient heterosis in desirable direction for yield components and traits related to earliness. Majority of the cross combinations succumb to fruit fly infestation and powdery mildew incidence. However, G-3×Sel-75-2-10 showed resistance against fruit fly infestation at both locations.